2007
DOI: 10.1038/sj.bjc.6603891
|View full text |Cite
|
Sign up to set email alerts
|

Liver cancer risk, coffee, and hepatitis C virus infection: a nested case–control study in Japan

Abstract: We examined hepatocellular carcinoma mortality in relation to coffee consumption and anti-hepatitis C virus (HCV) antibody seropositivity in a nested case -control study involving 96 cases. The multivariate-adjusted odds ratios (95% confidence interval) for daily coffee drinkers vs non-drinkers were 0.49 (0.25 -0.96), 0.31 (0.11 -0.85), and 0.75 (0.29 -1.92) in all cases, in HCV-positive and in HCV-negative individuals, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 12 publications
1
34
0
1
Order By: Relevance
“…A growing number of epidemiologic studies have observed a reduced risk of liver cancer with increased consumption of coffee (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15), and several meta-analyses have provided confirmation (16,17). Although several of the case-control (10,11,(13)(14)(15) and nested case-control (8, 9) studies took HCV or HBV infection status into consideration, most adjusted for HCV or HBV infection status in the model, and only a few observed risk among those who were HCV or HBV infection positive (8,10,13,14).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A growing number of epidemiologic studies have observed a reduced risk of liver cancer with increased consumption of coffee (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15), and several meta-analyses have provided confirmation (16,17). Although several of the case-control (10,11,(13)(14)(15) and nested case-control (8, 9) studies took HCV or HBV infection status into consideration, most adjusted for HCV or HBV infection status in the model, and only a few observed risk among those who were HCV or HBV infection positive (8,10,13,14).…”
Section: Discussionmentioning
confidence: 99%
“…Although an association between these beverages and liver cancer has been speculated (2,3), epidemiologic evidence is insufficient (4) and varies by beverage. Several cohort and case-control studies (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15) and meta-analyses (16,17) have reported a significant inverse association between coffee consumption and liver cancer, but none of these considered hepatitis virus infection status. Meanwhile, epidemiologic evidence for the association between green tea consumption and liver cancer is sparse (10,14,18), and little is known about its effects on liver cancer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In various studies including a large prospective study, patients with HCV-related liver disease with a regular coffee consumption show a lower rate of disease progression such as hepatic fibrosis [131][132][133] and HCC [134][135][136][137][138] . Recently, it was also reported that more than 3 cups per day coffee drinkers are three times more likely to have a virological response to peginterferon plus ribavirin treatment than non-drinkers [139] .…”
Section: Coffee Consumptionmentioning
confidence: 99%
“…scored liver tissue steatosis (0-3), inflammation (0-3), hepatocellular ballooning (0-2), and fibrosis (0-4), and calculated NAFLD activity score (NAS) for each patient. 3 CK-18 fragments values were correlated with NAS to predict the severity of liver disease.…”
Section: Noninvasive Diagnosis Of Nonalcoholic Fatty Liver Disease Usmentioning
confidence: 99%